Cover Image. Issue 5 (21st April 2021) - Wang, Si‐Qi; Shen, Yue; Li, Jing; Liu, Yun; Cheng, Li‐Sha; Wu, Sheng‐Di; She, Wei‐Min; Jiang, Wei
Abstract : Cover illustration: The cover image is based on the Original Article Entecavir‐induced interferon‐λ1 suppresses type 2 innate lymphoid cells in patients with hepatitis B virus‐related liver cirrhosis by Si‐Qi Wang et al., https://doi.org/10.1111/jvh.13476 .